Delusional infestation may be caused by recreational drug usage in some patients, but they may not disclose their habit. (1st January 2017) - Marshall, C. L.; Williams, V.; Ellis, C.; Taylor, R. E.; Bewley, A. P.
Summary: Background: Patients with delusional infestation (DI) believe that their skin is infested with organisms or inanimate particles, despite objective evidence to the contrary. Previous studies indicate a higher rate of recreational drug use among patients with DI. It is known that symptoms of infestation such as formication can be secondary to use of recreational drugs and alcohol. We carried out a pilot study observing the prevalence of recreational drug use in patients with DI. Aim: To observe the prevalence of recreational drug use in patients with DI. Methods: A retrospective review of 86 consecutive patient records was carried out over a 3‐year period (1 March 2012 to 1 March 2015) to determine current or previous recreational drug use. Additionally, 24 consecutive patients with DI attending clinic between 1 December 2014 and 1 March 2015 were prospectively offered a urine test for recreational drugs. Results: Of the 86 patients, 19 had recreational drug use documented in their medical notes (22.1%). Of the 24 patients offered a urine test, 18 accepted (75%); the remaining 6 patients agreed to provide a urine sample immediately after consultation, but did not do so. Of the 18 samples collected, 6 were positive (33.3% of completed tests) for recreational drugs. Cannabis was the most commonly used drug. Conclusions: This study indicates that the prevalence of recreational drug use in patients with DI is high, and that patients do not always disclose their habit. It is hoped that this pilot study will lead to further research into this finding.